War in the boats : my World War II submarine battles - Ruhe, William J. (Washington, D.C. : Brassey's, 1996)
"Reality and intensity are the chief watchwords of this unique and highly personal memoir of World War II submarine combat in the Southwest Pacific"--Seapower
Illustrations -- Foreword -- Preface -- The Rusty Old Sewer Pipe -- A Mare's Nest -- The Red Dragon -- Baptism -- Mutiny? -- Shallow Waters -- Wolfpack -- Disaster -- Epilogue -- Glossary -- Index
Includes index.
Keywords: Ruhe, William J; Ruhe, William J; United States. -- Navy -- Submarine forces -- History; United States. -- Navy -- Biography; United States. -- Navy; 1939-1945; World War, 1939-1945 -- Naval operations -- Submarine; World War, 1939-1945 -- Naval operations, American; World War, 1939-1945 -- Personal narratives, American; World War, 1939-1945 -- Campaigns -- Pacific Ocean; Sailors -- United States -- Biography; Guerre mondiale, 1939-1945; Guerre mondiale, 1939-1945; Guerre mondiale, 1939-1945 -- Campagnes et batailles; Marins -- v; Military campaigns; Military operations, Naval -- American; Military operations, Naval -- Submarine; Sailors; Armed Forces -- Submarine forces; Pacific Ocean; United States; Personal narratives; Biographies; History; Personal narratives -- American; Personal narratives; Biographies; 2; Biographies